(f o g)(x) or 'f composite g' is defined as f(g(x)). This means, for every 'x' in f(x), put in g(x). This means that:
'f composite g' = f(x^2+9). Now we place this into f, thus:
'f composite g' = ln(x^2+9)
-------
Hope this helps
2006-12-08 19:15:38
·
answer #1
·
answered by JSAM 5
·
0⤊
0⤋
Your first step is stating what (f o g)(x) means, so that's what we do.
(f o g)(x) is defined to be f(g(x)). Plugging in g(x) for the inside of the function f, we get
f(g(x)) = f (x^2 - 9)
And now, plugging in x^2 - 9 for every instance of x in the function of f, we get
ln(x^2 - 9)
That's our answer. (f o g) (x) = ln(x^2 - 9).
If you wanted to get technical, you can actually change the form of that.
ln(x^2 - 9) = ln ( [x-3][x+3] ) = ln (x-3) + ln (x+3)
2006-12-09 03:20:43
·
answer #2
·
answered by Puggy 7
·
2⤊
1⤋
basically f o g = f[g(x)] = ln [x^2 - 9]
2006-12-09 04:46:24
·
answer #3
·
answered by yasiru89 6
·
0⤊
0⤋
basically it looks like
ln (x^2 - 9)
there you go
2006-12-09 03:17:09
·
answer #4
·
answered by dark aran 2
·
0⤊
0⤋
simple :
ln (x^2 - 9) for sure
2006-12-09 03:41:54
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
fog => f [g(x)] => f [ x^2.9] => ln(x^2.9)
2006-12-09 03:17:23
·
answer #6
·
answered by Lady_Marmalade 2
·
0⤊
0⤋